Chemotherapy for upper gastrointestinal tumours. Issue 896 (1st June 2000) - Thomas, A L; O'Byrne, K; Steward, W P
Abstract : The aim of this review is to identify current chemotherapy treatment for tumours of the oesophagus, stomach, pancreas, and liver. The role of both neoadjuvant, adjuvant, and palliative chemotherapy regimens will be discussed. This review will be of interest to oncologists in clarifying current issues regarding chemotherapy, and to physicians in other medical specialties, to increase their general understanding of benefits and drawbacks of chemotherapy in this patient group.